2010
DOI: 10.1002/mds.23129
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q10‐responsive ataxia: 2‐year‐treatment follow‐up

Abstract: We assessed the clinical outcome after coenzyme Q(10) (CoQ(10)) therapy in 14 patients presenting ataxia classified into two groups according to CoQ(10) values in muscle (deficient or not). We performed an open-label prospective study: patients were evaluated clinically (international cooperative ataxia rating scale [ICARS] scale, MRI, and videotape registration) at baseline and every 6 months during a period of 2 years after CoQ(10) treatment (30 mg/kg/day). Patients with CoQ(10) deficiency showed a statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 45 publications
4
46
0
Order By: Relevance
“…They reported a significant improvement in all patients except in one. The best clinical response among all patients was demonstrated in a patient who showed only mild vermian atrophy (Pineda et al 2010). All patients with CoQ10 deficiency due to mutations in ADCK3 gene failed to improve and even worsened under treatment with the shorter chain ubiquinone analog, idebenone (Aure and Benoist 2004;Mollet et al 2008).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…They reported a significant improvement in all patients except in one. The best clinical response among all patients was demonstrated in a patient who showed only mild vermian atrophy (Pineda et al 2010). All patients with CoQ10 deficiency due to mutations in ADCK3 gene failed to improve and even worsened under treatment with the shorter chain ubiquinone analog, idebenone (Aure and Benoist 2004;Mollet et al 2008).…”
Section: Discussionmentioning
confidence: 93%
“…There is no consensus regarding the oral dose for treatment of CoQ10 deficiency, treatment protocols have not been standardized and results have not been uniform. CoQ10 supplementation has been tried in patients with ADCK3 gene-related ataxia (Lamperti et al 2003;Aure and Benoist 2004;Mollet et al 2008;Pineda et al 2010;Horvath et al 2012;Emmanuele et al 2012) in different regimens ranging from 5 to 30 mg/kg/day. Aure et al reported significant improvement in exercise tolerance and decrease of vomiting episodes under CoQ10 supplementation of 6 mg/kg/day.…”
Section: Discussionmentioning
confidence: 99%
“…87 Typically, doses in the range 5 to 30 mg/kg/d have been administered to patients with documented low levels of tissue CoQ 10 as well as those with a primary CoQ 10 deficiency. 25,88,89 In the absence of a demonstrable CoQ 10 deficiency, doses of 5 to 30 mg/kg/d may also be used in the treatment of cases of known and suspected mitochondrial disease. 25,78 In Parkinson disease, a plasma CoQ 10 level of 4.6 μmol/L was reported to be the most effective in slowing functional decline in patients.…”
Section: Coenzyme Q 10 Monitoring and Dosagementioning
confidence: 99%
“…Secondary CoQ 10 deficiency has also been associated with diverse mitochondrial diseases [Quinzii et al, 2006;Gempel et al, 2007;Montero et al, 2008;Haas et al, 2009;Cotan et al, 2011;Miles MV et al, 2011]. In all of these conditions, CoQ 10 supplementation partially improves symptoms [Montini et al, 2008;Pineda et al, 2010;Schon et al, 2010] and usually induces a return to normal growth and respiration in CoQ 10 -deficient fibroblasts [Lopez-Martin et al, 2007;Cotan et al, 2011]. Thus, adaption of somatic cells to a pathogenic mutation may affect both onset and course of CoQ 10 deficiency in each patient or animal model.…”
Section: Summarizing the Human Syndrome Of Coq 10 Deficiencymentioning
confidence: 99%